Knowledge, Attitude and Practices of Dental Patients About Cross-Infection and Infection Control - Meltem Tekbaş Atay; Mediha Büyükgöze Dindar (Ankara University, 2021)
Objectives: This study aimed to evaluate the patient's knowledge, attitude, and practice of cross-infection control in dentistry. Materials and Methods: This cross-sectional study was conducted at the Dentistry Faculty of........... University. A total of 250 patients (134 female and 116 male) aged 18 years and older (35.5±13.9) participated in the questionnaire containing questions to determine the knowledge, attitudes, and practices related to cross-infection and infection control. Required personal and socio-demographic data were obtained. Chi-square test was conducted for categorical variables. Kruskal Wallis and Mann Whitney U tests were used to compare questionnaire scores (p lt;0.05). Results: The majority of the participants (30.5%) reported that their sources of information on dental infection control were social media. Knowledge scores of females were statistically significantly higher than males (p=0.005) and participants living in the city were significantly higher than those living in the town (p=0.015). Knowledge scores of health-care workers were significantly higher than both other workers and unemployed/students (p=0.001, p=0.004, respectively). Regarding participants' attitudes and practices, only 29.2% of the participants questioned the dentists about the contagious disease, and only 36% asked about the sterilization method of the dental instruments. The majority of participants perceived that wearing gloves, masks, eyewear, and face shield would protect both patients and dentists. Conclusion: Participants in this study demonstrated a satisfactory level of knowledge about cross-infection and infection control methods in the nowadays' pandemic condition. However, dental health professionals should take additional efforts to educate and encourage dental patients.